Interpersonal Communication between Supervisors and Students in the Formation of Students' Characters - Asrizallis, Asrizallis (Civiliza Publishing, Indonesia., 2025)
The problem of interpersonal communication between mentors and students is a matter of great concern in character formation at Ar Risalah Padang Islamic Boarding School. This study aims to determine the interpersonal communication approach of mentors and students in character formation, to determine the interpersonal communication strategy of mentors and students in character formation, and to determine the supporting and inhibiting factors of interpersonal communication between mentors and students in character formation at Ar Risalah Padang Islamic Boarding School. This study uses a qualitative method with a descriptive approach). The data source was taken from ten informants through in-depth interviews selected using purposive sampling techniques, some informants are teachers and dormitory mentors and some are students at Ar Risalah Padang Islamic Boarding School. The results of the study indicate that the interpersonal communication approach between mentors and students in character formation is by conducting personal, persuasive and motivational communication as well as communication like a family. The interpersonal communication strategy between mentors and students in character building is by implementing rewards and punishments, implementing the 1 day 1 child program, and holding evaluation meetings.